Comparative evaluation of sterilization approaches in bitches - VERMA, PALLAVI; SINGH, TARUNBIR; GAHLOT, T K (The Indian Journal of Animal Reproduction, 2023)
Eighteen adult, clinically healthy, mongrel bitches were divied into 3 groups of 6 animals each and were subjected toovariohysterectomy (OH) through 2 approaches viz., minilaparotomy (ML T) through rightflank without external skin sutures.ML T through rightflank with skin sutures (modification of the former) and the conventional midventral laparotomy in the 3rdgroup. It was found that minimum complications, minimum time taken ( 18.33±0.988 minutes) and minimum cost(Rs. I 04.98±3.455) for surgery was for ML T for OH without skin sutures. On the other hand the conventional mid ventrallaparotomy for OH had maximum complications besides the longest duration of time (39.5±0.6 I 9 minutes) and maximum cost(Rs.230.22±17.208) for surgery.
Keywords: Sterilization; bitch